The role of breast cancer resistance protein (Bcrp/Abcg2) in triptolide-induced testis toxicity. Issue 5 (22nd June 2015) - Li, Chunzhu; Xing, Guozhen; Maeda, Kazuya; Wu, Chunyong; Gong, Likun; Sugiyama, Yuichi; Qi, Xinming; Ren, Jin; Wang, Guangji
Graphical Abstract: Abstract: Triptolide has been intensively studied in numerous preclinical and clinical assessments for immunosuppressive and anti-tumor activities. However, further clinical use is limited by the cumulative toxicity of triptolide in the testis and the mechanisms are poorly understood. In this study, we found significant triptolide accumulation in the testis, and further investigated the role of efflux transporters in its accumulation and toxicity. Chronic administration of triptolide induced time- and dose-dependent testicular injury and resulted in the accumulation of triptolide in the liver and testis, but not in the plasma. Using transporter-expressed cells, triptolide efflux was found in BCRP-expressing cells, which could be blocked by novobiocin (an inhibitor of BCRP) in accumulation assays. Triptolide also displayed apically directed transport across BCRP-expressing cell layers in transwell assays, strongly supporting that triptolide is a substrate of BCRP. Bcrp knockout mice (Bcrp −/− ) were further used to examine the effects of triptolide. Knockout of Bcrp aggravated triptolide-induced testicular injury and increased the testis content and testis to plasma ratio of triptolide in Bcrp −/− mice. Notably, triptolide decreased the transcript and protein levels of Bcrp in the testis, which may be due to the downregulation of RNA polymerase II. In conclusion, as a substrate of BCRP, triptolide decreased the expression of Bcrp and RNA polymerase II in the testis, and further increased the testis content and enhanced its testicular toxicity, which contributes to the cumulative toxicity of triptolide in the testis.